Pengaruh User-Generated Content, Social Proof dan Brand Image terhadap Keputusan Pembelian di Kota Malang (Studi pada Konsumen Produk Make Over) - Ervina, Mafisatul; Pardiman, Pardiman; Normaladewi, Andi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study was conducted to analyze the influence of User-Generated Content, Social Proof, and Brand Image on the purchase decisions of Make Over products among consumers who are active on social media. The background of this research is based on the increasing use of social media, which plays an important role in shaping consumer purchase decisions, especially in the cosmetics industry. This research uses a quantitative approach with a survey method by distributing questionnaires to 140 respondents in the Malang area. The data were analyzed using multiple linear regression analysis. The results show that User-Generated Content has no significant effect on purchase decisions. However, Social Proof and Brand Image have a positive and significant influence. These findings suggest that Make Over should improve its Social Proof and Brand Image as part of its marketing strategy to influence consumer purchase decisions. Keywords: User-Generated Content, Social Proof, Brand Image, Purchase Decision, Make Over